2003
DOI: 10.1046/j.1464-5491.2003.00953.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum interleukin‐6 levels and bone mineral density at the femoral neck in post‐menopausal women with Type 1 diabetes

Abstract: Although our study had a small sample size, we found that post-menopausal women with Type 1 diabetes mellitus present lower bone mass and higher serum bioactive IL-6 levels than matched healthy controls, but we were unable to find a correlation between these two parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 22 publications
2
14
3
Order By: Relevance
“…Theoretically, several mechanisms may be suggested to be responsible for low bone mass in DM, such as insulinopenia (14,15), microangiopathy (16,17) and increased interleukin elevation (18). In turn, the lack of metabolic control may potentially affect also the maintenance of bone mass, interfering not only with the equilibrium of mineral metabolism (19,20), but also with bone remodeling activity (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, several mechanisms may be suggested to be responsible for low bone mass in DM, such as insulinopenia (14,15), microangiopathy (16,17) and increased interleukin elevation (18). In turn, the lack of metabolic control may potentially affect also the maintenance of bone mass, interfering not only with the equilibrium of mineral metabolism (19,20), but also with bone remodeling activity (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…Autoimmune destruction of the pancreatic beta cells by infiltrating immune cells triggers pancreatic and systemic upregulation of inflammatory cytokines in humans [43-45] and in animal models of STZ-induced diabetes [46]; moreover, T1D subjects with poor glycemic control exhibit higher levels of inflammation compared to well-controlled subjects [45]. Inflammatory cytokines that are systemically upregulated in T1D subjects, such as tumor necrosis factor alpha (TNF-α), interleukin 1 (IL-1) and interleukin 6 (IL-6) have been demonstrated to have negative effects on osteoblast proliferation and differentiation in vitro , as well as inhibition of bone healing in vivo [47-50].…”
Section: Effects Of Type 1 Diabetes On Osteoblastsmentioning
confidence: 99%
“…IL-6 also plays a role in diabetes. It has been shown that postmenopausal women with type 1 diabetes present higher serum bioactive IL-6 levels than matched healthy controls [29]. Moreover, IL-6 polymorphism seems to be a genetic susceptibility factor for the progression of diabetic nephropathy [16].…”
Section: Testing the Hypothesismentioning
confidence: 99%